2006
DOI: 10.1002/cphc.200500389
|View full text |Cite
|
Sign up to set email alerts
|

The Leading Role of Association in Framework Modification of Highly Siliceous Zeolites with Adsorbed Methylamine

Abstract: Affinity index (AT value), adsorption heat, X-ray diffraction (XRD), and 13C and 29Si magic-angle spinning (MAS) NMR, FTIR, and Raman spectroscopies were used to study the interaction of highly siliceous MFI-, FAU-, and FER-type zeolites with adsorbed methylamine (MA). Compared with the data for methanol, the much higher AT values and adsorption heats, and significant changes in XRD patterns, 29Si MAS NMR spectra, and FTIR spectra for the zeolites after adsorption of MA, revealed a strong hydrogen-bonding inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Strongly basic zeolites are attractive candidates, but such materials are notoriously difficult to make due to the strong inherent acidity of aluminosilicates. Several research groups have endeavored to produce strongly basic zeolites by treating zeolites with amines, but to date there is little compelling evidence that nitrogen is incorporated into zeolite frameworks. Here, we detail synthesis, NMR spectroscopy, and calculations showing that nitrogen adds to both surface and interior oxygen while preserving the zeolite framework.…”
mentioning
confidence: 99%
“…Strongly basic zeolites are attractive candidates, but such materials are notoriously difficult to make due to the strong inherent acidity of aluminosilicates. Several research groups have endeavored to produce strongly basic zeolites by treating zeolites with amines, but to date there is little compelling evidence that nitrogen is incorporated into zeolite frameworks. Here, we detail synthesis, NMR spectroscopy, and calculations showing that nitrogen adds to both surface and interior oxygen while preserving the zeolite framework.…”
mentioning
confidence: 99%
“…On the other hand, as we previously reported [ 8 ], n-octylamine can also produce a silica nitridation [ 54 , 55 ]. In a previous paper, Han et al [ 55 ] investigated interactions between methylamine and zeolites.…”
Section: Resultsmentioning
confidence: 54%
“…On the other hand, as we previously reported [ 8 ], n-octylamine can also produce a silica nitridation [ 54 , 55 ]. In a previous paper, Han et al [ 55 ] investigated interactions between methylamine and zeolites. They concluded that the strong hydrogen bonding interaction results in the H atom of the amine group attacking the Si–O framework to form a Si–O...H...N bond, which leads to the formation of Si–N bonds in the zeolites.…”
Section: Resultsmentioning
confidence: 54%
“…Complementary fast (30 kHz) MAS 1 H NMR measurements confirmed the co-intercalation of CH 3 NH 2 in the fulleride salt (Figure S1). They showed the presence of a sharp resonance at 5.5 ppm, attributed to the −NH 2 protons and shifted downfield relative to that in uncoordinated CH 3 NH 2 (3.9 ppm), consistent with the expected cooordinative bonding to K + ions. Further resonances are also present at 3.4, 2.8, and 0.5 ppm and are attributed to the −CH 3 protons.…”
mentioning
confidence: 63%